Evaluation of Antibacterial and Antibiofilm Activity of Biogenic Silver Nanoparticles and Gentamicin Against Staphylococcus aureus Isolated from Caprine Mastitis - AL-Dujaily, Ali H; Mahmood, Alaa K (The Iraqi Journal of Veterinary Medicine, 2022)
The goal of this study was to assess the antibacterial efficiency of biogenic silver nanoparticles (AgNPs) and gentamicin against Staphylococcus aureus that can form biofilms. The characterization of AgNPs‎ was confirmed by the scanning electron microscope (SEM) which was spherical and homogenous in form, with a diameter between 25 and 45 nm. The X-ray diffraction (XRD) presented the size of AgNPs to be 50 nm. Energy dispersive spectroscopy (EDS) was used to examine the presence of elemental silver. The three-dimensional structure of silver nanoparticles was discovered using an atomic force microscope (AFM), with a diameter of 47.18 nm on average. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) of AgNPs and gentamicin against S. aureus isolated from caprine mastitis were determined using the microdilution assay. The checkerboard microdilution technique was utilized to inspect the synergistic antibacterial activity of AgNPs with gentamicin utilizing the fractional inhibitory concentration index (FICI). The antibiofilm capability of AgNPs was also investigated. The results indicate that AgNPs generated by biosynthesis are antibacterial against S. aureus. Moreover, AgNPs and gentamicin exhibit synergistic action. The study's findings suggest that biogenic AgNPs may act as anti-biofilm agents and treat mastitis caused by S. aureus. In conclusions biosynthesized AgNPs exhibit strong antibacterial and antibiofilm effectiveness and synergistic activity when combined with gentamicin.